ANALISIS IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DI SEKOLAH DASAR NEGERI PISANG CANDI 1 MALANG - Yuli Ani Setyo Dewi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2014)
This study uses a qualitative descriptive method. Data collection used in the research is observation, interviewing, and documentation. The focus of the research in collecting and analysing the data about the implementation of KTSP in The State Elementary School Pisang Candi 1 Malang .The data analysis states that the implementation of the curriculum is divided to two stages which are the implementation of school and class levels. Some supporting factors in the implementation of KTSP in The State Elementary School Pisang Candi 1 are the infrastructure of permanent buildings and good condition of the classrooms, the teachers who teach professionally with alot of teaching experiences and also the principal always gives moral support to the teachers which is motivation to increase the human resource. The preventing factors in the implementation in KTSP in The State Elementary School Pisang Candi 1 Malang are that the teachers are still lacking of understanding about KTSP and the minimum facility of the teaching media. And also the school committee which is lack of understanding in the development of KTSP.